2011
DOI: 10.33584/rps.15.2011.3222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of defoliation strategies on the productivity, population and morphology of plantain (Plantago lanceolata)

Abstract: This trial provided information about effects of defoliation frequency, defoliation intensity and winter management (grazing or rest) on the productivity, morphology and plant population of a 3-year-old plantain (Plantago lanceolata) stand. Plant population density declined drastically over time independently of grazing management, with the greatest decrease in summer. Winter grazing had a critical effect on the productivity and population remaining 6 months later. Frequent grazing during summer increased plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Within pure swards it is well established that grazing chicory or plantain during late autumn and winter has substantial negative effects on yield, plant density and crop persistence (Ayala et al 2011;Li et al 1997).…”
Section: Grazing Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Within pure swards it is well established that grazing chicory or plantain during late autumn and winter has substantial negative effects on yield, plant density and crop persistence (Ayala et al 2011;Li et al 1997).…”
Section: Grazing Managementmentioning
confidence: 99%
“…Chicory and plantain are both high yielding, summer active perennial herbs which can maintain high nutritive values during warm summer conditions (Lee et al 2015;Minneé et al 2013;Powell et al 2007). However, the persistence of both chicory and plantain are reduced markedly when they are grazed during winter (Ayala et al 2011;Li et al 1997), and therefore they are not particularly compatible with winter active grass species.…”
Section: Introductionmentioning
confidence: 99%
“…A factorial (2 × 2) block design with three replicates was used to evaluate a combination of two defoliation intensities (3 or 10 cm post-grazing residual height, referred as severely (S) or lightly (L) grazed) and two frequencies of defoliation (each 21 or 42 days referred as frequent (F) or infrequent (I) grazing). During winter (June to early September) pasture was not grazed, based on a previous report (Ayala et al 2011) that described critical effects of winter grazing on productivity and population of a 3-year-old plantain stand. The grazing schedule resumed in early September and was followed until March.…”
Section: Methodsmentioning
confidence: 99%
“…While plantain is not commonly used in Uruguay, preliminary reports have demonstrated its potential as an alternative forage species (Barrios 2006). The study of defoliation strategies have been focused on a research program of INIA Uruguay determining the critical effects of winter grazing on plantain productivity and population (Ayala et al 2011). The objective of this trial was to provide additional information about the effect of defoliation intensity and frequency on productivity and plant population changes of plantain pasture.…”
Section: Introductionmentioning
confidence: 99%
“…Plantain contributed between 35-70% of the +P swards from autumn to late spring of 2016, but had diminished to <20% by autumn 2017. While this proportion can be expected to increase again during the second winterspring (Woodward et al 2013), a longer-term pattern of decline for plantain has been observed elsewhere under rotational winter cutting/grazing of monocultures (Sanderson et al 2003;Ayala et al 2011), leading Cranston et al (2015) to suggest that it is not compatible with winter-active grasses.…”
Section: Botanical Compositionmentioning
confidence: 99%